Cone Outer Segment Extracellular Matrix as Binding Domain for Interphotoreceptor Retinoid-Binding Protein - Garlipp, Mary Alice (2012)
Cones are critically dependent on interphotoreceptor retinoid-binding protein (IRBP) for retinoid delivery in the visual cycle. Cone-dominant vertebrates offer an opportunity to uncover the molecular basis of IRBP's role in this process. Here, we explore the association of IRBP with the interphotoreceptor matrix (IPM) of cones vs. rods in cone dominant retinas from chicken (Gallus domesticus), turkey (Meleagris gallopavo), and pig (Sus scrofa). Retinas were detached and fixed directly or washed in saline prior to fixation. Disassociated photoreceptors with adherent matrix were also prepared. Under 2 mM CaCl(2), insoluble matrix was delaminated from saline washed retinas. The distribution of IRBP, as well as glycans binding peanut agglutinin (cone matrix) and wheat germ agglutinin (rod/cone matrix), was defined by confocal microscopy. Retina flat mounts showed IRBP diffusely distributed in an interconnecting, lattice-like pattern throughout the entire matrix. Saline wash replaced this pattern with fluorescent annuli surrounding individual cone outer segments. In isolated cones and matrix sheets, IRBP colocalized with the peanut agglutinin binding matrix glycans. Our results reveal a wash-resistant association of IRBP with a matrix domain immediately surrounding cone outer segments. The cone matrix sheath may be responsible for IRBP-mediated cone targeting of 11-cis retinoids.